THE INFLUENCE OF MULTIMEDIA INTERACTIVE BY USING GUIDED INQUIRY LEARNING MODEL TO STUDENTS’ CRITICAL THINKING SKILL - khoiru nisa; pramudi yanti; rini marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
ABSTRACTCritical thinking skill is important for students to overcome their daily life problem . Result of observation of class VIII  SMP Negeri 1 Pardasuka, showed that students’ critical thinking skill was still low. The purpose of this research is to find out  the influence of multimedia interactive by using guided inquiry learning model to students’ critical thinking skill. The aspecs of students critical thingking observed  were to identify, to give example, to make differences, to interpretation, to generallized, to give assumption. Students activities observed were to give idea, to disscuss, to present, to answer questions, to ask question. This research used   pretest posttest group non- equivalent designed. The sampel were students of class VIII E and class VIII F  chosen at cluster randomly. The quantitative data was obtained from N-gain, and was analyzed by t-test at realibility of 5 %. Qualitative data were  the  students’ activity collected  during  process  which was  analyzed in the percentage of average. Students’ questionnaire responses on  using   multimedia interactive with guided inquiry learning  was analyzed descriptively. The  N-gain analysis of students critical thinking was  0,4 in average, meaning  that the use of multimedia interactive  using guided inquiry learning model  influenced significantly toward students’ critical thinking. In term of students activities, asking questions aspect reach the highest (54,5%).